2010
DOI: 10.1093/jb/mvq125
|View full text |Cite
|
Sign up to set email alerts
|

Increased globotriaosylceramide levels in a transgenic mouse expressing human  1,4-galactosyltransferase and a mouse model for treating Fabry disease

Abstract: Fabry disease is a lysosomal storage disorder caused by an α-galactosidase A (α-Gal A) deficiency and resulting in the accumulation of glycosphingolipids, predominantly globotriaosylceramide (Gb3). A transgenic mouse expressing the human α-Gal A R301Q mutant in an α-Gal A-knockout background (TgM/KO) should be useful for studying active-site-specific chaperone (ASSC) therapy for Fabry disease. However, the Gb3 content in the heart tissue of this mouse was too low to detect an ASSC-induced effect. To increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…Despite the signifi cant accumulation of Gb 3 and lysoGb 3 in kidney of Fabry mice shown in this study and others ( 17 ) and the pathological changes in kidney tissues ( 8,10 ), there are no obvious clinical abnormalities such as proteinuria and renal failure, which are common in Fabry patients, reported in Fabry mice. A systematic characterization …”
Section: Discussioncontrasting
confidence: 65%
“…Despite the signifi cant accumulation of Gb 3 and lysoGb 3 in kidney of Fabry mice shown in this study and others ( 17 ) and the pathological changes in kidney tissues ( 8,10 ), there are no obvious clinical abnormalities such as proteinuria and renal failure, which are common in Fabry patients, reported in Fabry mice. A systematic characterization …”
Section: Discussioncontrasting
confidence: 65%
“…Transgenic (TgG3S) mice expressing human G3S, generated in our previous study [18], were maintained by breeding with wild-type C57BL/6 mice. The G3Stg/GLAko mouse line was generated by crossbreeding male TgG3S mice and homozygous female GLAko mice [6].…”
Section: Methodsmentioning
confidence: 99%
“…We previously generated human Gb3 synthase (G3S)-transgenic mice (TgG3S mice) with elevated Gb3 levels in major organs [18]. In this study, we prepared a new mouse line (G3Stg/GLAko) by crossbreeding TgG3S and GLAko mice to obtain a phenotypic model for Fabry disease.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we show the utility of pharmacoperone drugs to correct disease by rescuing PM expression rescue of a misfolded GPCR. Previous work using mouse models of lysosomal storage diseases demonstrated that pharmacoperone treatment can stabilize inactive misfolded soluble lysosomal enzymes and improve their function (18)(19)(20). These studies provided proof of principle that pharmacoperones can stabilize a misfolded protein in vivo.…”
Section: Comparison Of Gnrhr Mouse Mutants Reveals the Consequences Ofmentioning
confidence: 85%